ANALISIS STRUKTUR KELEMBAGAAN DEWAN KETAHANAN NASIONAL DAN SEKRETARIAT JENDERAL DEWAN KETAHANAN NASIONAL SEBAGAIMANA DIATUR DALAM KEPUTUSAN PRESIDEN 101 TAHUN 1999 - Fadillah Haris Unamsila; Ferry Edwar (Reformasi Hukum Trisakti, 2023)
Presidential Decree Number 101 of 1999 concerning the National Defense Council and the Secretariat General of the National Defense Council, according to the author, it is implied that there are 2 state institutions / government agencies, namely the National Defense Council and the Secretariat General of the National Defense Council. However, when examined from the organizational structure, the position of the Secretariat General of the National Defense Council, led by the Secretary General of the National Defense Council, is organizationally still responsible to the chairman of the National Defense Council, namely the president, so that a contradiction arises between the title of Presidential Decree 101 which states that there are 2 state institutions / government agencies with a structure organizations that only mention the existence of 1 State Institution, namely the National Defense Council, also found problems regarding the accountability system at the Wantannas Secretariat General related to Presidential Regulation Number 29 of 2014 concerning Government Agency Performance Accountability Systems (SAKIP). The question arises why Presidential Decree No. 29 of 2014 is only applied to the Wantannas Secretariat General as LPNK, why it is not also applied to Wantannas as LNS. It is necessary to immediately change the form of the regulation which originally was a Presidential Decree to become a Presidential Regulation and it is also necessary to revitalize the institution which originally had two institutions in one regulation to become only one institution without reducing the main tasks and functions of the previous institution. It is necessary to make improvements to performance accountability in government agency performance accountability reports (SAKIP) in accordance with Presidential Regulation No. 29 of 2014 concerning Government Agency Performance Accountability Systems.